EXPRESSION OF UNIQUENESS IN ENGLISH-LANGUAGE TOURISM DISCOURSE - Vasylenko, Halyna (SWorldJournal, 2025)
The article highlights the linguistic and stylistic features of expressing the uniqueness of tourist destinations in English-language tourism texts. Samples of analysis are given to illustrate the widespread use of adjectivized phrases, defining relative